Protein Degradation during Reconsolidation as a Mechanism for Memory Reorganization - Kaang, Bong-Kiun; Choi, Jun-Hyeok (Frontiers in Behavioral Neuroscience, 2011)
Memory is a reference formed from a past experience that is used to respond to present situations. However, the world is dynamic and situations change, so it is important to update the memory with new information each time it is reactivated in order to adjust the response in the future. Recent researches indicate that memory may undergo a dynamic process that could work as an updating mechanism. This process which is called reconsolidation involves destabilization of the memory after it is reactivated, followed by restabilization. Recently, it has been demonstrated that the initial destabilization process of reconsolidation requires protein degradation. Using protein degradation inhibition as a method to block reconsolidation, recent researches suggest that reconsolidation, especially the protein degradation-dependent destabilization process is necessary for memory reorganization.